Optimal load suitability based RAT selection for HSDPA and IEEE 802.11e - Cabral, O.
Networks of the future envisage a network-of-wireless-networks that provide the end user the means to connect to the best available network at anytime and at any place. However, equally challenging for the operators is to provide these services at low cost in an era where spectral resources are a premium. This paper investigates cooperation between networks based radio access technology (RAT) selection algorithm that uses suitability to optimize the choice between WiFi and high speed downlink packet access (HSDPA). It has been shown that this approach has the potential to provide gain by allocating a user terminal to the most preferred network based on traffic type and network load. Optimal load threshold values that maximise the total QoS throughput for the given interworking scenario are 0.6 and 0.53 for HSDPA and WiFi, respectively. This corresponds to a CRRM gain on throughput of 80% with 60 users.